2010
DOI: 10.1111/j.1464-410x.2009.09139.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal medullary carcinoma: molecular, pathological and clinical evidence for treatment with topoisomerase‐inhibiting therapy

Abstract: Study Type – Aetiology (case series)
Level of Evidence 4 OBJECTIVE To present the molecular rationale and potential clinical benefit of topoisomerase II (TopoII)‐inhibiting therapy for renal medullary carcinoma (RMC), a rare but extremely lethal form of kidney cancer that classically afflicts young men with sickle‐cell trait. The current therapeutic approach with these aggressive tumours is radical nephrectomy followed by systemic chemotherapy, but the prognosis remains dismal. MATERIALS AND METHODS The whole‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 16 publications
3
32
0
Order By: Relevance
“…The most significant clinical challenge presented by RMC is that chemo-, immuno-and radiotherapy have all been unsuccessful for the treatment of RMC, based on previous studies (4,5,(17)(18)(19)(20)(21)(22). Therefore, an early diagnosis may improve the survival rates of patients with RMC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most significant clinical challenge presented by RMC is that chemo-, immuno-and radiotherapy have all been unsuccessful for the treatment of RMC, based on previous studies (4,5,(17)(18)(19)(20)(21)(22). Therefore, an early diagnosis may improve the survival rates of patients with RMC.…”
Section: Discussionmentioning
confidence: 99%
“…The histopathological features of RMC include epithelial cells with reticular, adenoid cystic plasia, and prominent inflammation (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…58 The therapeutic experience with other subtypes of RCC, such as papillary RCC, is limited. 27,54,59 In the future, the stratification of subtypes of RCC and evaluation of responses of patients with different subtypes of RCC to targeted therapies will be critical for success of the targeted therapy.…”
Section: Resultsmentioning
confidence: 99%
“…A separate study identified the absence of SMARCB1/INI1 with loss of heterozygosity at the SMARCB1/INI1 gene locus on chromosome 22. 44 SMARCB1 is a tumor suppressor gene involved in chromatin remodeling, cell cycle control, and regulation of cytoskeletal dynamics. Finally, a study by Schaeffer et al 45 revealed high expression of topoisomerase II in a patient who achieved 9 months of complete remission with doxorubicin.…”
Section: Geneticsmentioning
confidence: 97%